1994
DOI: 10.3109/10428199409056282
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid Resistance in Childhood Leukemia

Abstract: Glucocorticoids (GC) are being used in the treatment of childhood leukemia for several decades, most successfully in newly diagnosed acute lymphoblastic leukemia (ALL). However, GC resistance is seen in 10-30% of untreated ALL patients, and is much more frequent in relapsed ALL and in acute nonlymphoblastic leukemia (ANLL). Sensitivity or resistance to GC can be measured using a cell culture drug resistance assay. For this purpose, we use the colorimetric methyl-thiazol-tetrazolium (MTT) assay. We have shown t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(67 citation statements)
references
References 93 publications
2
65
0
Order By: Relevance
“…[13][14][15] Furthermore, reduced affinity of GR for its ligand, defective translocation of GR across the nuclear membrane and binding of the GR to the GRE are also not thought to be of major importance in glucocorticoid resistance in leukaemia. 1 A number of other possible mechanisms of resistance to glucocorticoids may occur downstream of the action of the receptor. The inhibition of poly-ADP-ribose-polymerase (PARP) by benzamide, 3-aminobenzamide and nicotinamide has been shown to enhance GC induced apoptosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15] Furthermore, reduced affinity of GR for its ligand, defective translocation of GR across the nuclear membrane and binding of the GR to the GRE are also not thought to be of major importance in glucocorticoid resistance in leukaemia. 1 A number of other possible mechanisms of resistance to glucocorticoids may occur downstream of the action of the receptor. The inhibition of poly-ADP-ribose-polymerase (PARP) by benzamide, 3-aminobenzamide and nicotinamide has been shown to enhance GC induced apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…In ALL approximately 20% of patients are resistant to glucocorticoids at time of presentation but in those patients that relapse up to 80% are resistant. 1,2 The actions of glucocorticoids are mediated through specific intracellular glucocorticoid receptors (GR) found in almost all mammalian cells. The human GR is an acidic phosphoprotein with a molecular weight of 97 kDa.…”
Section: Introductionmentioning
confidence: 99%
“…Using dexamethasone binding assays, it was shown that decreased binding of dexamethasone was related to GC resistance in childhood ALL. Although this finding was regarded to be due to a lower expression level of the GR, 32 it may alternatively be related to a reduced rate in complex maturation due to defects in one of these molecules other than just the expression level of these molecules. However, to study the formation of the GR-(co)chaperone complex will be very difficult when using patient material, as the different stages of this complex will pass quickly.…”
Section: Figurementioning
confidence: 96%
“…Several studies with respect to specific targets like the glucocorticoid receptor (GR) and its splice variants, to proteins involved in the activation process of the GR and genetic variants of drug resistance genes or of the GR itself did not show any correlation between the results and the GC resistance. [21][22][23][24][25][26][27][28][29][30][31] In contrast to many proteome screening studies in human tissues, the advantage of the current study is that proteins were isolated from purified leukaemic cells that had all been processed and stored in the same manner. The minimum percentage of leukaemic blasts in the bone marrow of patients investigated was 77% before gradient centrifugation.…”
Section: Discussionmentioning
confidence: 99%